On the Mechanisms of Ability Peer Effects - Alexandra de Gendre; Nicolás Salamanca (Institute of Labor Economics (IZA), 2020)
Studying with higher ability peers increases student performance, yet we have little idea why. We exploit random assignment of students to classrooms and find positive peer effects on test scores. With rich data on nineteen potential mechanisms, we then estimate how effects on attitudes, parents, and teachers could drive these results. Higher-achieving peers reduce student effort, increase student university aspirations, increase parental time investments and parental strictness, and have precise null effects elsewhere. None of these mechanisms, however, explain our peer effect on test scores. Our results highlight promising avenues for understanding ability peer effects.
Keywords: I23; I26; D13; 330; random assignment; standardized test; parental investments; school inputs; mediation analysis